Circulating cytokine and chemokine profiles of Trypanosoma cruzi-infected women during pregnancy and its association with congenital transmission - Volta, Bibiana (2021)
Trypanosoma cruzi, the causative agent of Chagas disease, can be transmitted to the offspring of infected women, which constitutes an epidemiologically significant parasite transmission route in non-endemic areas. It is relevant to evaluate differentially expressed factors in T. cruzi-infected pregnant women as potential markers of Chagas congenital transmission.MethodsCirculating levels of twelve cytokines and chemokines were measured by ELISA or cytometric bead array in T. cruzi-infected and uninfected pregnant women in their second trimester of pregnancy, and control groups of T. cruzi-infected and uninfected non-pregnant women.ResultsT. cruzi-infected women showed a pro-inflammatory Th1-biased profile, with increased levels of TNF-α, IL-12p70, IL-15 and MIG. Uninfected pregnant women presented a biased response towards Th2/Th17/Treg profiles, with increased plasma levels of IL-5, IL-6, IL-1β, IL-17A and IL-10. Finally, we identified that high parasitemia together with low levels of TNF-α, IL-15, and IL-17, low TNF-α/IL-10 ratio, and high IL-12p70 levels are factors associated with an increased probability of Chagas congenital transmission.ConclusionsT. cruzi-infected pregnant women who did not transmit the infection to their babies exhibited a distinct pro-inflammatory cytokine profile that might serve as a potential predictive marker of congenital transmission.